LRP-1-mediated endocytosis regulates extracellular activity of ADAMTS-5 in articular cartilage. - Yamamoto, K; Troeberg, L; Scilabra, S; Pelosi, M; Murphy, C; Strickland, D; Nagase, H (2013)
Aggrecan is a major matrix component of articular cartilage, and its degradation is a crucial event in the development of osteoarthritis (OA). Adamalysin-like metalloproteinase with thrombospondin motifs 5 (ADAMTS-5) is a major aggrecan-degrading enzyme in cartilage, but there is no clear correlation between ADAMTS-5 mRNA levels and OA progression. Here, we report that post-translational endocytosis of ADAMTS-5 by chondrocytes regulates its extracellular activity. We found 2- to 3-fold reduced aggrecanase activity when ADAMTS-5 was incubated with live porcine cartilage, resulting from its rapid endocytic clearance. Studies using receptor-associated protein (RAP), a ligand-binding antagonist for the low-density lipoprotein receptor-related proteins (LRPs), and siRNA-mediated gene silencing revealed that the receptor responsible for ADAMTS-5 clearance is LRP-1. Domain-deletion mutagenesis of ADAMTS-5 identified that the noncatalytic first thrombospondin and spacer domains mediate its endocytosis. The addition of RAP to porcine cartilage explants in culture increased the basal level of aggrecan degradation, as well as ADAMTS-5-induced aggrecan degradation. Notably, LRP-1-mediated endocytosis of ADAMTS-5 is impaired in chondrocytes of OA cartilage, with ∼90% reduction in protein levels of LRP-1 without changes in its mRNA levels. Thus, LRP-1 dictates physiological and pathological catabolism of aggrecan in cartilage as a key modulator of the extracellular activity of ADAMTS-5.